Terapi Non-Farmakologi pada Pasien Insomnia: A Literature Review - Putri, Meilani; Daulay, Suryani Agustina; Carolia, Novita; Sukohar, Asep (Medula, 2024)
Insomnia is a condition characterized by difficulty initiating sleep despite having adequate time and opportunity. Globally, the majority of insomnia sufferers are women, with approximately 10% of the world’s population estimated to experience severe insomnia. The management of insomnia typically begins with the principles of Consultation, Information, and Education (CIE). In cases of severe insomnia, further intervention often involves pharmacological therapy through medication. The primary class of drugs prescribed for insomnia patients generally belongs to the benzodiazepine group, which acts as a central nervous system depressant, muscle relaxant, and sedative. However, pharmacological treatment should always be complemented with non-pharmacological therapy. Notably, non-pharmacological interventions serve as the first-line treatment for patients with mild to moderate insomnia. This review article aims to evaluate the effectiveness of various non-pharmacological therapies for managing insomnia, which is recognized as the most prevalent sleep disorder worldwide. The literature review was conducted by searching databases such as PubMed, Google Scholar, and ScienceDirect using the keywords “Insomnia,” “Therapy,” and “Non-Pharmacological.” Based on the search results, seven relevant articles were selected for review. The findings from these studies indicate that effective non-pharmacological interventions for insomnia management include Cognitive Behavioral Therapy for Insomnia (CBT-I), hypnotherapy, audiovisual stimulation, aerobic and endurance exercises, acupuncture, and Pre-Sleep Dim Light Therapy (LT).